Assessment of aluminosilicate raw material used in Lebanon: Effect of curing. Issue 1 (25th January 2019) - Saba, Marianne; Georges, Najib; Absi, Joseph
Abstract: This research assesses the effect of curing and porosity on the microstructure and mechanical properties of aluminosilicate‐based material. Within the first 24 hours of production, all samples endured the same influence of curing temperature that was set to 60°C. Throughout the aging process, all samples were kept at ambient temperature. Simultaneously, the impacts on the microstructure and mechanical properties were studied. The results indicated that while aging and with the same physical conditions, the dissolution, polymerization, and precipitation processes of the geopolymerization reaction were quite different. This variation was mainly affected by the porous and nonporous characteristics of the aluminosilicate material produced. From a mechanical point of view, the optimum samples obtained were the ones having low porosity, where the mechanical properties such as load at failure reached 59 MPa after being cured for 28 days.